The Influence Of Innovation, Work Enthusiasm And Work Facilities On Employee Quality At The Ministry Of Religion Office Muara Enim District - Mohd Bahrun; Sulbahri Majdir; Harun Samsuddin (Journal of Indonesian Management, 2023)
The aim of this research is to determine and analyze the influence of innovation, work enthusiasm and work facilities, both partially and simultaneously, on the quality of employees at the Muara Enim Regency Ministry of Religion office. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, coefficient of determination, partial tests and simultaneous tests. The research results showed that innovation had a significant effect on the quality of employees at the Muara Enim Regency Ministry of Religion office. Work morale has a significant effect on the quality of employees at the Muara Enim Regency Ministry of Religion office. Work facilities have a significant effect on the quality of employees at the Muara Enim Regency Ministry of Religion office. Innovation, work enthusiasm and work facilities have a significant effect together on the quality of employees at the Muara Enim Regency Ministry of Religion office.